Comparative Study of Tang Poetry Translation from a Medio-Translatological Perspective: The Cases of Chen Guojian and Guillermo Dañino - Siyu, Liu; Danna, Chen (Sinología hispánica. China Studies Review, 2026)
As a crown jewel of Chinese cultural heritage, Tang poetry is of exceptional significance in terms of translation and international dissemination. Its presence in Spanish-speaking countries has developed through nearly a century of translation practice. Among the many contributors, the translations by Chinese Hispanist Chen Guojian and Peruvian sinologist Guillermo Dañino are widely recognized as foundational contributions. This study employs the theoretical frameworks of Medio-translatology, the Three Beauties Principle, and Paratext Theory to conduct a systematic textual and paratextual comparison between these two Spanish translations. The analysis seeks to uncover the distinctive translation approaches and underlying motivations of each translator. Furthermore, through examining book reviews and conducting reader surveys, the research investigates the reception of both translated versions within the Hispanic world.